Design of livestock mortality insurence system as a tool of rosk guarantee for sustainability the smallholder beef cattle in West Java (risk identification in the smallholder beef cattle) - Hasni Arief; Sri Rahayu; Cecep Firmansyah (Proceedings of AICS - Social Sciences, 2013)
Under conditions where a very small scale of farming, death of cattle can be no sustained business continuity factors that can disrupt the economy of the family. Further efforts to beef self-sufficiency will be threatened. Consider this, the necessary existence of an insurance system that can provide a guarantee for the sustainability of beef cattle livestock people. The purpose of this study were: 1) generate information about the risks involved in beef cattle farming in the context of changes in the current economic environment, 2) generate a description of the strategies and practices of governance risks run by actors livestock beef cattle at the moment, and 3) generate valuation and risk indicators for the feasibility of applying the insurance system in livestock beef cattle. The study was conducted in three (3) areas: District of Bandung, District of Subang, and District of Ciamis for eight months (since April to November 2012).The research method used was a survey method, which used technique of sampling is multistage random sampling. The number of samples used in this study as the primary data source as many as 150 people breeder. The data were analyzed descriptively by tabulation triangulation. The results showed that the dominant risk is a problem faced by farmers feed (forage) and diseases (diarrhea, flu, and bloating). To that end, death insurance deemed necessary because it was an case, very rare (incidence average once in 5 years). Nevertheless, the demand for insurance cattle ranchers (not specific: livestock mortality insurance) is very high, 90% of total survey respondents farmer wants a livestock insurance. Mainstay in the management of risk is to diversify its business, farming or fishing; reduce inputs, both the number and kind, and formed a partnership system. How risk management is closely linked to socio-economic conditions that farmers (individual attributes). Breeders realized that farming of beef cattle an economic sector heavily laden with risk conditions. Therefore, the farmers consider that the risk (losses) not yet at the level of troubling.Keywords: Livestock insurance, risk management, beef cattle